Spatial resolution of HIV-1 post-entry steps in resting CD4 T cells - Swetha Ananth; Ina Ambiel; Sandra Schifferdecker; Thorsten G. Müller; Paul R. Wratil; Ernesto Mejias-Perez; Hans-Georg Kräusslich; Barbara Müller; Oliver T. Keppler; Oliver T. Fackler (Cell Reports, 2024)
Summary: Resting CD4 T cells resist productive HIV-1 infection. The HIV-2/simian immunodeficiency virus protein viral accessory protein X (Vpx) renders these cells permissive to infection, presumably by alleviating blocks at cytoplasmic reverse transcription and subsequent nuclear import of reverse-transcription/pre-integration complexes (RTC/PICs). Here, spatial analyses using quantitative virus imaging techniques reveal that HIV-1 capsids containing RTC/PICs are readily imported into the nucleus, recruit the host dependency factor CPSF6, and translocate to nuclear speckles in resting CD4 T cells. Reverse transcription, however, remains incomplete, impeding proviral integration and viral gene expression. Vpx or pharmacological inhibition of the deoxynucleotide triphosphohydrolase (dNTPase) activity of the restriction factor SAM domain and HD domain-containing protein 1 (SAMHD1) increases levels of nuclear reverse-transcribed cDNA and facilitates HIV-1 integration. Nuclear import and intranuclear transport of viral complexes therefore do not pose important blocks to HIV-1 in resting CD4 T cells, and the limitation to reverse transcription by SAMHD1’s dNTPase activity constitutes the main pre-integration block to infection.